Inovasi Pembelajaran Pendidikan Agama Islam Melalui Program Merdeka Belajar Kampus Merdeka Berbasis Outcome Based Education - Nur Hadi, Muhammad; Supriyatno, Triyo; Marno; Syaifullah (Mu'allim, 2024)
Independent learning, independent campus is a contemporary learning concept that is able to facilitate innovation in Islamic Religious Education learning, because in the independent learning program, learning can be done in the classroom or outside the classroom, even learning is carried out in the real world of work. The aim of this research is to finding an innovation strategy for learning Islamic Religious Education through an independent learning program on an independent campus based on Outcome Based Education (OBE) that is capable of creating student-centered learning. This research uses a qualitative approach with a library research type, data collection is carried out using documentation, and data analysis is carried out in three stages, namely data condensation, data presentation and conclusion drawing. The results of the research show that the Islamic Religious Education learning innovation strategy is implemented using the project based learning (PBL) learning method based on Outcome Based Education which is carried out through eight programs, including: Student Exchange, Internships, Teaching Assistance in Education Units, Research, Independent Study, Entrepreneurship, Real Work Lectures, and Humanitarian projects.